68.3: Next Generation Liquid Optically Clear Adhesives. Issue 1 (1st July 2013) - Lu, Daniel; Wang, James; Li, Cristiano; Yuan, Jimmy; Sawanobori, Junichi; Liu, Gina; Jia, Ruby; Litke, Alan; Levandoski, Michael; Chi, Sarah; Malanaphy, Patrick; Serenson, James
Abstract: Liquid optically clear adhesives (LOCAs) are being used to attach various components in display assemblies to significantly enhance the viewer experience, display performance, and reliability. In this paper, we will discuss Henkel's latest technology development on LCD full lamination solutions including stress‐free LCD lamination, innovative primer technique to solve shadow curing issues, material and processing solutions to achieve excellent edge definition, and cleaner solution to address LOCA cleaning and reworking challenges.